Enhanced ocean connectivity and volcanism instigated global onset of Cretaceous Oceanic Anoxic Event 2 (OAE2) ∼94.5 million years ago - Li, Yong-Xiang; Liu, Xinyu; Selby, David; Liu, Zhonghui; Montañez, Isabel P.; Li, Xianghui (Earth and planetary science letters, 2022)
•We report the first high-resolution Os isotope record of the OAE2 interval in Southern Hemisphere.•The Os data indicate episodes of successively intensifying volcanism proximal to the onset of OAE2.•An interval of cooling equivalent to the Plenus Cold Event of Northern Hemisphere is recognized.•The CIEs of OAE2 intervals of the Iona-1 core (WIS, North America) and Yezo Group (Japan) are refined.•Enhanced ocean connectivity was essential for the global onset of OAE2 at ∼94.5 Ma. Oceanic Anoxic Event 2 (OAE2) exemplifies an episode of global oceanographic and climatic changes in the mid-Cretaceous greenhouse. However, the timing and mechanism of its global initiation remain elusive. Here we report a high-resolution initial osmium isotope (187Os/188Osi, Osi) and δ13Corg record from an expanded OAE2 interval in southern Tibet, China that was deposited in the Southern Hemisphere. The Osi record documents episodic, intensifying volcanism with the highest intensity episode marked by a large Osi excursion at ∼94.5 Ma and a subsequent ∼200 kyr Osi minimum concomitant with a cooling interval, which is broadly synchronous with the Plenus Cold Event (PCE) recorded in the Northern Hemisphere. Also, the large Osi excursion lags the onset of OAE2 by ∼50 kyr and occurred during a near synchronous global transgression based on high-resolution correlation with other major OAE2 records. These results are interpreted as indicating that enhanced ocean connectivity played a critical role in helping trigger the global onset of OAE2 at ∼94.5 Ma.